Eksplorasi Nilai Budaya Sasak dalam Pendidikan Karakter Melalui Aksi P5 di Sekolah Dasar - Kasim, Sunardy (Yayasan Pendidikan Intan Cendekia, 2023)
This study aims to measure and demonstrate the differences in students' understanding of science concepts before and after using gamification-based learning media. The research employs a quantitative approach with a pre-experimental design, specifically the One Group Pretest-Posttest, which involves measuring students' understanding both before and after the application of the learning method. The study sample consists of 31 fifth-grade students from SDN 5 Mataram. Data was collected through tests and analyzed using the paired sample t-test to assess the effectiveness of gamification-based learning media in enhancing students' comprehension of science concepts. The findings indicate a highly significant difference in students' understanding of science concepts before and after the implementation of gamification-based learning media. This is supported by the probability result (Sig. 2-tailed) = 0.000, which is smaller than ? = 0.05, and even smaller than ? = 0.01, confirming that gamification has a significant impact on improving students' comprehension. Therefore, it can be concluded that gamification-based learning media is effective in helping students better understand science concepts. Consequently, teachers are encouraged to integrate gamification-based learning into science lessons. This approach not only makes learning more engaging and enjoyable but also enhances students' motivation, confidence, active participation, and interest in the subject. By providing a more interactive learning experience, students can more easily connect science concepts to real-life situations, ultimately leading to better learning outcomes